"Pre‐emptive strike"—the case for early treatment of hepatic sinusoidal obstruction syndrome with defibrotide. Issue 7 (14th March 2018) - Rajagopal, Revathi; Phillips, Marianne B.; Gottardo, Nicholas G.
Abstract: The initial signs of hepatic sinusoidal obstruction syndrome (HSOS) can be challenging to recognize in children, especially outside the hematopoietic stem cell transplantation setting. To assist clinicians to promptly identify HSOS, the European Society for Blood and Marrow Transplantation has proposed pediatric HSOS diagnostic criteria which emphasize unexplained consumptive and transfusion‐refractory thrombocytopenia. To highlight the importance of these "bellwether" early signs of HSOS and the efficacy of pre‐emptive treatment with defibrotide, we describe the case of a child with a right 11th rib primitive neuroectodermal tumor who developed HSOS following focal radiotherapy and actinomycin‐D treatment.